Quantitative T2* relaxation time analysis of articular cartilage of the tibiotalar joint in professional football players and healthy volunteers at 3T MRI. Issue 2 (9th May 2017) - Behzadi, Cyrus; Maas, Kai‐Jonathan; Welsch, Goetz; Kaul, Michael; Schoen, Gerhard; Laqmani, Azien; Adam, Gerhard; Regier, Marc
Abstract : Purpose: To compare T 2 * relaxation times of the tibiotalar cartilage between professional football players and matched healthy male volunteers. Materials and Methods: Twenty‐two ankles of professional football players (24.3 ± 3.8 years) and 20 age‐ and body mass index‐matched healthy individuals (25.6 ± 2.4 years) were investigated. The study protocol consisted of multiplanar T 1 ‐weighted, fat‐saturated proton‐density weighted (Pdw) and a 3D multiecho T 2 * sequence with 22 echo times (4.6–53.6 msec). The articular cartilage was subdivided into six segments. Regions of interest were manually drawn in three zones (lateral, central, medial). Differences and confidence intervals were estimated applying a random effects models. Fixed effects were professional football players versus healthy individuals and areas. The random effect was defined as the person cluster of the different individuals. Results: T 2 * values were significantly prolonged in football players compared to male volunteers in all predefined cartilage segments (mean, 17.5 vs. 15.5 msec; P < 0.001). In both groups, the highest relaxation times were found in the lateral zone, with statistically higher relaxation times in professional football players (18.5 vs. 16.5 msec, P = 0.003). Separate evaluation revealed the longest relaxation times in the posterior tibiotalar cartilage, with 21.0 msec for professional football players compared to 19.4 msec for healthy volunteers ( P = 0.064). Conclusion: Based on these initial results, T 2 * values of the tibiotalar cartilage seem to be elevated in professional football players compared to healthy volunteers. Prospective longitudinal studies should be encouraged to show if these results represent early subtle cartilage lesions prior to clinical manifestation or rather temporary adaptation related to daily high‐level loading. Level of Evidence: 1 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2018;47:372–379.